Technical review of the da Vinci surgical telemanipulator. Issue 4 (20th November 2012) - Freschi, C.; Ferrari, V.; Melfi, F.; Ferrari, M.; Mosca, F.; Cuschieri, A.
Abstract Background The da Vinci robotic surgical telemanipulator has been utilized in several surgical specialties for varied procedures, and the users' experiences have been widely published. To date, no detailed system technical analyses have been performed. Methods A detailed review was performed of all publications and patents about the technical aspects of the da Vinci robotic system. Results Published technical literature on the da Vinci system highlight strengths and weaknesses of the robot design. While the system facilitates complex surgical operations and has a low malfunction rate, the lack of haptic (especially tactile) feedback and collisions between the robotic arms remain the major limitations of the system. Accurate, preplanned positioning of access ports is essential. Conclusion Knowledge of the technical aspects of the da Vinci robot is important for optimal use. We confirmed the excellent system functionality and ease of use for surgeons without an engineering background. Research and development of the surgical robot has been predominant in the literature. Future trends address robot miniaturization and intelligent control design. Copyright © 2012 John Wiley & Sons, Ltd.